(untitled) ("Temas Sociais" Journal, 2025)
This article addresses the challenges that end-of-life situations pose to the professional practice of social workers in a society where death is often silenced or marginalized. Based on an interdisciplinary literature review, a theoretical framework is proposed through systemic and ecological models, aiming to understand terminally ill individuals within their socio-cultural, relational, and institutional contexts. The paper argues that effective social work intervention in this field requires not only technical expertise but also personal development and emotional readiness from professionals. Furthermore, it advocates for the integration of this subject matter into the academic curricula of Social Work, fostering more humane and holistic practices at the end of life.